Systemic lupus erythematosus in an 11-year-old girl. - Farinelli, P.; Delrosso, G.; Boggio, P.; Griffanti, P.; Leigheb, G. (European Journal of Pediatric Dermatology, 2005)
An 11-year-old girl presented asthenia, arthralgies, photosensibility, Raynaud's phenomenon, erythematous spots on the zygomatic-malar area and on the back of the nose, erythemato-edematous and cyanematous spots with ulcerations and crusts on the finger-tips, erythematous lesions and keratotic follicular papulae on the gluteal region and the arms and erythematous spots in the oral cavity accompanied by burning feeling. Autoimmune evaluation and a skin bioptic sample confirmed the suspicion of SLE. The presence of a pericardiac ubiquitary effusion with initial signs of cardiac tamponage needed pericardiocentesis and an immunosuppressive attack therapy. Children affected by SLE need careful and close monitoring, better if they are hospitalized in specialized structures fully organized and able to deal with possible complications, which are by no means rare.